Susceptibility-Weighted Imaging in Grading of Infiltrative Glial Tumors - Ocak, Firuze; Yıldız, Mehmet Erdem; Dinçer, Alp (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2020)
ABSTRACT Purpose: Histopathological and radiological examination is necessary for the evaluation of tumor types and staging. Histopathologic examination is considered as the gold standard, while the radiological examination is used for preoperative evaluation. The purpose of the present study was to evaluate susceptibility-weighted imaging (SWI) the in grading of infiltrative glial tumors. Materials and Methods: The SWI sequences in pre-operative magnetic resonance imaging (MRI) images were retrospectively assessed in a total of 67 patients (mean age, 36.7 years; age range, 4–79 years; 29 female, 38 male) who were diagnosed with a glial tumor based on histopathological examination. The numbers of punctate intratumoral susceptibility sign (ITSS) in the SWI sequence in the tumors were determined by two radiologists on a consensus-based approach. Lesions with no ITSS were graded as Grade 0, while those having 1–5, 6–15, >15 ITSS were categorized as Grade 1, Grade 2, and Grade 3, respectively. No susceptibility was classified as ITSS, “non-punctate with blurred margins” and diffuse susceptibility were categorized as >15. ITSS grades were compared to the results of histopathological grading and diagnosis. Results: The sensitivity, specificity, negative predictive value, and positive predictive value of the presence of ITSS regarding differentiating high and low-grade glial tumors were 97.6%, 88%, 95.65%, and 93.18%, respectively. Conclusion: In diffuse glial tumors, while the presence of ITSS is indicative of high-grade tumors, its absence is associated with low-grade tumors. These data suggest that the presence rather than the number of ITSS yields more information on the grade of this type of tumor.